Ruislag Tanah Wakaf: Pelaksanaan Peraturan Pemerintah Nomor 25 Tahun 2018 di Bukit Baru Kota Pangkalpinang Ditinjau dari Istihsan - Rizki Pratama; Winarno Winarno; Tauratiya Tauratiya (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2023)
Ruislag waqf land is one example of the many human needs currently so that the government makes regulations to adapt to the needs of the community. The existence of regulations regarding Waqf Land Ruislag which are contained in Government Regulation Number 25 of 2018 concerning the Implementation of Waqf Land Ruislag, has created a new color in society. Along with the understanding of people who follow only one school of thought or the general public in implementing waqf. The problem in this article is, how is the implementation of Waqf Land Ruislag in Bukit Baru Pangkalpinang City, Bangka Belitung Islands Province Based on Government Regulation Number 25 of 2018 and how is the Implementation of Waqf Land Ruislag in Bukit Baru Pangkalpinang City, Bangka Belitung Islands Province Based on Government Regulation Number 25 of 2018 Reviewed from Istihsan. This research is qualitative research using a Juridical-Empirical approach. The source of this research is primary data obtained from observations and interviews with the Head of the local Religious Affairs Office as well as observations and interviews with the chairman of the nadzir and the treasurer of the mosque under study. Then it is also equipped with supporting secondary data. Rules regarding Government Regulation Number 25 of 2018 concerning the Implementation of Waqf Land Ruislag. Case studies in Bukit Baru, Pangkalpinang City, show that the procedures and conditions set out in it are aimed at utilizing waqf land (ruislag) by creating facilities that support religious interests. Istihsan's review of the implementation of the Government Regulation in Bukit Baru, Pangkalpinang City, is a form of collective responsibility for the condition of waqf land which has no use or value in it to cover the harm in an effort to utilize waqf land (ruislag) and maintain waqf property so that it is useful for the benefit of general (Istihsan bil Al-Maslahah).